2018
DOI: 10.1101/446708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing Influence of Sensory and Motor Cortical Input on Striatal Circuitry and Choice Behavior

Abstract: The striatum is the main input nucleus of the basal ganglia and is a key site of sensorimotor integration. While the striatum receives extensive excitatory afferents from the cerebral cortex, the influence of different cortical areas on striatal circuitry and behavior is unknown. Here we find that corticostriatal inputs from whisker-related primary somatosensory (S1) and motor (M1) cortex differentially innervate projection neurons and interneurons in the dorsal striatum, and exert opposing effects on sensory-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 86 publications
0
9
1
Order By: Relevance
“…In contrast, a previous study reported that neurons in somatosensory cortex preferentially targeting D1 direct pathway neurons trigger actions (Wall et al, 2013). However, neurons in whisker-related primary somatosensory cortex innervate parvalbumin (PV)-expressing interneurons as well (Lee et al, 2019), therefore S1FL might have the potential to improve performance by suppressing undesired actions. Additionally, this study found that optogenetic stimulation of S1 corticostriatal afferents led to less responses in the tactile discrimination task, which is different from our results.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, a previous study reported that neurons in somatosensory cortex preferentially targeting D1 direct pathway neurons trigger actions (Wall et al, 2013). However, neurons in whisker-related primary somatosensory cortex innervate parvalbumin (PV)-expressing interneurons as well (Lee et al, 2019), therefore S1FL might have the potential to improve performance by suppressing undesired actions. Additionally, this study found that optogenetic stimulation of S1 corticostriatal afferents led to less responses in the tactile discrimination task, which is different from our results.…”
Section: Discussionmentioning
confidence: 88%
“…Putative multi-modality neurons [30], [31], [32], [33] in motor-related cortices could take over this task of multisensory-integration projecting to the primary motor cortex. More recently, a significant role in sensorimotor integration has been attributed to the striatum [34]. If kinaesthetic-and visual information are processed in the same way during motor preparation, we proposed above, both, seeing a movement and feeling a passive movement should enhance the corticospinal excitability.…”
Section: Introductionmentioning
confidence: 87%
“…Previous work has shown strong cortical and thalamic connectivity to PV+ striatal neurons (Arias-García et al, 2018;Assous & Tepper, 2019;Choi et al, 2019;Lee et al, 2019;Melzer et al, 2017;Ramanathan et al, 2002), which are more responsive than SPNs (Gittis et al, 2010;Koós et al, 2004;Mallet et al, 2005;Planert et al, 2010;Tecuapetla et al, 2007). Also, connections between SPNs (Chuhma, Tanaka, Hen, & Rayport, 2011;Czubayko & Plenz, 2002;Tecuapetla et al, 2007;Tunstall, Oorschot, Kean, & Wickens, 2002) whose lateral inhibition (Burke et al, 2017;Dobbs et al, 2016;Guzmán et al, 2003) and their differential responses to afferent inputs, dopamine (DA) and acetylcholine (ACh) may also help to achieve this result (Assous & Tepper, 2019;Dobbs et al, 2016;Flores-Barrera, Vizcarra-Chacón, Bargas, Tapia, & Galarraga, 2011;Flores-Barrera, Vizcarra-Chacón, Tapia, Bargas, & Galarraga, 2010;Garas et al, 2016;García-Vilchis et al, 2019;Gittis et al, 2010;Guzmán et al, 2003;Taverna, Canciani, & Pennartz, 2007;Tecuapetla et al, 2007;Tecuapetla, Koós, Tepper, Kabbani, & Yeckel, 2009).…”
Section: Microcircuit Modifications After Optogenetic Activation Ofmentioning
confidence: 99%